DEGRADASI MEKANIK BETON AKIBAT INTRUSI AIR LAUT - hanafi ashad; Fauzan Hamdi (Magister Teknik Sipil Pps Universitas Muslim Indonesia, 2022)
The problem that occurs in concrete buildings in the coastal environment is that concrete damage occurs due to degradation of concrete intruded by sea water. Damage to concrete due to seawater, consists of 3 (three) parts, namely: the part of the concrete that is submerged in sea water (sub-meged), the part of the concrete that is exposed to sea tides and the part of the concrete that is exposed to splashes of sea water. The damage to concrete discussed in this study is the mechanical degradation of concrete due to seawater intrusion on the part submerged in seawater. Damage can occur to concrete due to the reaction between aggressive seawater which has intruded into the concrete with compounds in the concrete which causes the concrete to lose some of its mass, lose its strength and stiffness and accelerate the weathering process. The results of this study indicate that the reduction in compressive strength of concrete due to seawater intrusion tends to show a logarithmic graph. In this case, the compressive strength of normal concrete will lose 50% when the concrete is immersed in sea water for 19,031 days. Normal quality concrete f'c = 25 MPa experienced mechanical degradation due to seawater intrusion, in this case the compressive strength of concrete was 12.063% when soaked for 28 days and 16.809% when soaked for 90 days.